Media health literacy predicts preventive health behaviors: findings from a nationally matched survey - Ashtari, Shadee Hall; Rodrigues Recchia, Daniela (Frontiers in Digital Health, 2025)
ObjectivesTo produce the first validated measurement of Adult Media Health Literacy (AMHL) and examine associations between scores on the new index and eight specific health behaviors and outcomes.MethodsA cross-sectional survey was conducted in 2023 with a non-probability sample of 589 U.S. adults ages 25–64, matched to national census demographics for age, gender, race, and education. The survey included the AMHL Index and outcome measures on smoking, vaping, vaccination, annual exams, mammography, colon cancer screening, and chronic health status. The predictive validity of the Index was evaluated using PLS-SEM. Covariate-adjusted linear and logistic regression models assessed the relationship between participants’ composite scores and reported health behaviors and outcomes.ResultsAll Index indicators demonstrated no collinearity concerns and a reliable measurement. Higher AMHL scores were significantly associated with higher odds of preventive health behaviors. A single-point increase on the Index was independently associated with increased odds of vaccination, mammography, and annual exam attendance, and decreased odds of smoking and vaping.ConclusionsThe study provides the first validated AMHL measure and evidence for the independent role media literacy plays as a social determinant of health. Multi-sector intervention opportunities are discussed.